Simulação do comportamento de íons em solos altamente intemperizados utilizando o modelo de capacitância constante - Silva, Luiz Gabriel da (Universidade Federal de São Carlos, 2017)
Agriculture is a very important economic activity in Brazil, and almost all cultures are grown directly on the soil. Thus, improve the knowledge of soil behavior is fundamental for the improvement of agricultural practices potentially harmful to the environment. The acric Oxisols are highly weathered soils, present in large and important productive productive regions of Brazil, and there are few studies using surface complexation models for description of ion adsorption processes in these soils. This work aimed at verifying the adequacy of the constant capacitance model in describing the adsorption of copper, cadmium, nickel and zinc in Latosols acric. This verification was done by analysing simulation residues and comparing surface potencial simuations with the values of PESN. All cations used are plant nutrients or important trace elements with respect to environmental contamination. In this work three soils were considered,Oxisol acric (LVwf), Oxisoil acric (LAw) and Eutric Kandiudalf (NVef). Measurements of their chemical (CEC, pH, Organic carbon, etc,), mineralogical (kaolinite and gibbsite) and physical (distribution of particle size and specific surface area) properties as well as adsorption, were obtained from literature. The adsorption envelope measurements collected in the literature were generally very consistent, and the cadmium and zinc measures are more behaved distribution in relation to other cations. Capacitance constant model were performed by a iterative computer program named FITQL. The constant capacitance model proved reasonably adequate to simulate the behavior of all the cations of the study. Simulations for nickel were relatively inconsistent regarding the experimental measurements. In most cases it was not possible to make appropriate distinctions between measurements and simulations for surface and depth, between the three concentrations of supporting electrolyte. All simulations of waste presented well-defined structure, unlike that normally expected. This may occur mainly due to methodological errors or errors inherent to the model, however, examples were not found in the literature regarding the waste generated by the simulation model for a proper comparison.
Keywords: Latossolo; Ácrico; Modelo de capacitância constante; Oxisoil; Acric; Constant capacitance model; CIENCIAS AGRARIAS